Determinants of Capital Structure: An Empirical Analysis of UK Organisations. - Gundroo, Shadaab/ SG (2009)
In modern day finance, capital structure remains one of those issues under much controversy despite extensive research from academics and practitioners alike. There is a number of existing theories and empirical work on capital structure but as of yet no universal model has been found. The aim of this paper is to analyze the determinants of the capital structure of 73 UK companies over a 5 year period (2004-2008). This study adds to the relatively limited empirical literature on factors influencing capital structure decisions in the UK by including an updated data set and a more extensive set of explanatory variables. The analysis is conducted using multiple regression methods on secondary data. The study demonstrates a disparity between the empirical results and theoretical predictions on some variables against total debt (TD). The results of the cross-sectional OLS regression & linear regression (using robust standard errors) shows that both the pecking order theory (profitability, liquidity, size, volatility) and the trade-off theory (asset structure, tax shield, growth opportunities and product uniqueness) are pertinent to the UKs company’s capital structure. However, not all these variables proved to be significant. The results shows the importance of the variables varied according to the type of debt (short vs. long). This is also highlighted in the correlation matrix as correlations for short-term and long-term debt do vary quite significantly on many of the variables. The evidence from the empirical findings show that in general across all three models (Total, Long-term & Short-term debt) that profitability, liquidity, tangibility and size are the most important variables of capital structure considerations for UK managers. The least important variables on average were shown to be tax shield, volatility and growth factors as illustrated by the significance levels. Overall, I conclude the effect of industry classification has a limited effect on debt ratios especially in relation to short-term debt. This work has contributed to the capital structure literature, however due to the inherent limitations further work is still required, perhaps with more rigorous empirical tests. #Key words: Capital Structure, Debt, Equity, Modigliani and Miller, Trade-off, Pecking order, Agency costs #